2018
DOI: 10.3389/fnmol.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

CB1R-Mediated Activation of Caspase-3 Causes Epigenetic and Neurobehavioral Abnormalities in Postnatal Ethanol-Exposed Mice

Abstract: Alcohol exposure can affect brain development, leading to long-lasting behavioral problems, including cognitive impairment, which together is defined as fetal alcohol spectrum disorder (FASD). However, the fundamental mechanisms through which this occurs are largely unknown. In this study, we report that the exposure of postnatal day 7 (P7) mice to ethanol activates caspase-3 via cannabinoid receptor type-1 (CB1R) in neonatal mice and causes a reduction in methylated DNA binding protein (MeCP2) levels. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 163 publications
(328 reference statements)
4
42
1
Order By: Relevance
“…The inhibition of CDK5 activity by roscovitine (seliciclib) in P7 mice also rescues neurodegeneration in neonatal mice and augments pERK1/2, pCREB, and Arc signalling deficits and the loss of Rac1 gene expression, synaptic plasticity, and behavioural defects in adult mice exposed to alcohol at P7. These data indicate that the CB 1 receptor‐mediated (Subbanna et al, ; Subbanna et al, ) up‐regulation of CDK5/p25 activity followed by the inhibition of pERK, pCREB, and the epigenetic suppression of Arc (Subbanna et al, ) and Rac1 expression is responsible for the long‐lasting neurobehavioural defects observed in adult mice exposed to alcohol at P7.…”
Section: The Role Of the Ecb System During Development And Its Functimentioning
confidence: 92%
“…The inhibition of CDK5 activity by roscovitine (seliciclib) in P7 mice also rescues neurodegeneration in neonatal mice and augments pERK1/2, pCREB, and Arc signalling deficits and the loss of Rac1 gene expression, synaptic plasticity, and behavioural defects in adult mice exposed to alcohol at P7. These data indicate that the CB 1 receptor‐mediated (Subbanna et al, ; Subbanna et al, ) up‐regulation of CDK5/p25 activity followed by the inhibition of pERK, pCREB, and the epigenetic suppression of Arc (Subbanna et al, ) and Rac1 expression is responsible for the long‐lasting neurobehavioural defects observed in adult mice exposed to alcohol at P7.…”
Section: The Role Of the Ecb System During Development And Its Functimentioning
confidence: 92%
“…Therefore, we next evaluated the role of caspase 3 activation in p35 protein degradation using a broadspectrum caspase inhibitor (Q-VD-OPh). We have previously shown that preadministration of an optimum dose (1 mg/kg) of Q-VD-OPh before ethanol treatment in P7 mice effectively prevented the formation of CC3 without altering BELs [11,34]. Thus, in the present study, a 1 mg/kg dose of Q-VD-OPh was used.…”
Section: Q-vd-oph Prevents P35 Protein Degradation and Generation Of mentioning
confidence: 93%
“…Postnatal ethanol exposure reduced Rac1 expression to adulthood via epigenetic mechanisms; postnatal ethanol-induced deficits in activity-regulated cytoskeleton-associated protein (Arc), pCREB, and Rac1 levels in adult mice were rescued by pretreatment with RV We have previously demonstrated that P7 ethanol treatment causes persistent impairment of pCREB followed by Arc expression in adult animals [11,37]. To understand whether RV treatment at P7 rescues these signaling deficits in the adulthood, we analyzed Arc and pCREB protein levels in HP tissues of adult mice treated with RV at P7.…”
Section: Downstream Activities Of Cdk5 In P7 Ethanol-treated Mice Is mentioning
confidence: 99%
See 2 more Smart Citations